Treasures of the Holy Sepulchre (The Biblical archaeology review, 2025)
Through January 5, 2026 The Frick Collection New York City, New York frick.org More than 40 precious artifacts from the Church of the Holy Sepulchre in Jerusalem are currently on display at the Frick in New York City. These treasures date from the 17th and 18th centuries, when various European Catholic rulers donated them to […]